A series of selective and sensitive fluorescent sensors based on a thiophen-2-yl-benzothiazole unit for Hg2+. (14th January 2016) - Mei, Qunbo; Tian, Ruqiang; Shi, Yujie; Hua, Qingfang; Chen, Chen; Tong, Bihai
Abstract : Different types of fluorescent probes for Hg 2+ based on the 5-thiophen-2-yl-benzothiazole derivatives (TBT, CTBT, DTBT andNTBT ) were realized by changing the subsituents, including the fluorescence quenching probe, the fluorescence enhancement probe and the ratiometric fluorescent probe. Abstract : Different types of fluorescent probes for Hg 2+ based on the 5-thiophen-2-yl-benzothiazole derivatives (TBT, 2-thiophen-2-yl-benzothiazole;CTBT, 9-(5-benzothiazol-2-yl-thiophen-2-yl)-9 H -carbazole;DTBT, 2-(5-acenaphthen-5-yl-thiophen-2-yl)-benzothiazole; andNTBT, 6-(5-benzothiazol-2-yl-thiophen-2-yl)-2-hexyl-benzo[de]isoquinoline-1, 3-dione) were realized by changing the subsituents. Multisignaling changes were observed through UV-vis absorption and fluorescence spectra upon addition of Hg 2+ . The addition of Hg 2+ onTBT induced a remarkable OFF/ON-type fluorescence signaling behavior. With the introduction of electron-donating carbazole, the detection behavior ofCTBT was just the reverse of whatTBT displayed, while a ratiometric fluorescent probe based onDTBT for Hg 2+ was prepared by introducing the weak electron-drawing group acenaphthene. Moreover, the dichloromethane solution ofCTBT andDTBT showed a distinct color change from colorless to yellow with the addition of Hg 2+, which indicated that these two probes would facilitate the naked-eye detection of Hg 2+ . However, both UV-vis absorption and fluorescence spectra ofNTBT with strong electron-withdrawing substituents showed no obvious change upon addition of Hg 2+ . It would be concluded that the electronic properties of the molecule was one of the vital factors in designing chemosensor molecules.